Sharia-Based Management and Marketing Strategies for MSMEs: Enhancing Warung Sate Madura Performance in Support of the SDGs - Muhammad Rizal; Muthoifin; Sondos Jehad Shnewra (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to analyze the implementation of management and marketing strategies in Micro, Small, and Medium Enterprises (MSMEs), with a focused case study on Warung Sate Madura Cak Khoirul in Wonogiri. Theoretical framework: The research adopts a theoretical framework grounded in MSME marketing strategies and Islamic economic principles, emphasizing ethical conduct, fairness, and social responsibility. These principles align with the Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty), Goal 8 (Decent Work and Economic Growth), Goal 9 (Industry, Innovation, and Infrastructure), and Goal 12 (Responsible Consumption and Production). Literature review: The literature review encompasses previous findings on the role of digital marketing, especially social media, in MSME growth, as well as the significance of sharia-based management in sustaining ethical business practices. Methods: This study uses a qualitative descriptive method with data obtained through direct observation and interviews with the business owner, enabling an in-depth understanding of operational strategies. Results: The findings show that Warung Sate Madura Cak Khoirul successfully applies simple yet impactful marketing strategies. These include word-of-mouth promotion, consistent use of social media, price fairness, friendly service, and consistent product quality, all of which build strong customer loyalty. The business also reflects Islamic values such as honesty (ṣidq), trustworthiness (amānah), and responsibility (mas’ūliyyah), creating a business model that is not only profitable but ethically sound. Implications: This study implies that integrating Islamic ethical values with marketing efforts contributes to sustainable business growth and resilience in competitive markets. Furthermore, it supports SDG initiatives by fostering inclusive economic participation, ethical consumerism, and community empowerment through MSMEs. Novelty: The novelty of this research lies in its exploration of how sharia-compliant management and marketing strategies can simultaneously enhance MSME performance and advance sustainability goals—an area seldom examined in previous literature on local food-based enterprises.